Optimal season for discriminating C3 and C4 grass functional types using multi-date Sentinel 2 data - Cletah Shoko; Onisimo Mutanga; Timothy Dube (GIScience & Remote Sensing, 2020)
The ability of remote sensing systems to optimally discriminate and map C3 and C4 grass species varies over time, due to environmental changes, which influence their phenological, physiological and morphological characteristics. In this regard, the discrimination of C3 and C4 grasses is insufficient when using a single image acquired at a specific period. In this study, multi-date Sentinel 2A MultiSpectral Instrument (MSI) data were explored to determine the optimal period for classifying and mapping Festuca costata, C3 and Themeda Triandra, C4 grasses in the montane grasslands of South Africa. The study further assessed how seasonal variations in species classification can be explained by climatic variability (rainfall and temperature). Results showed that image acquisition dates influence the discrimination accuracy, spatial representation of the two grass species, as well as the performance of spectral bands. The winter period also presents a better temporal window for discriminating C3 and C4 target grass species, with higher overall classification accuracies (between 91.8% and 95.3%), than summer (between 81.4% and 90.3%). Lower omission (between 2.8% and 11.6%) and commission (between 2.5% and 14.2%) errors were also observed when discriminating using winter images, as compared to those acquired in summer. Summer images showed large grass species areal coverage (e.g. in November and March, C3 and C4 covered ±25%), whereas in winter (mainly August), a notable decrease was observed. Overall, findings of the study have demonstrated the relevance of multi-date Sentinel data in discriminating C3 and C4 grass species. There is, however, a need to explore the classification ability of Sentinel 2 derivatives, especially during early summer and winter fall.